2002
DOI: 10.1089/08892220260139495
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and HIV Pharmacotherapy

Abstract: Alcohol consumption by individuals infected with HIV is an important medical management issue with significant implications for the effectiveness of antiretroviral therapy as well as an important evolving field of HIV research. Alcohol consumption is a risk factor for poor medication adherence and can modify liver drug metabolism, both of which can lead to the emergence of drug-resistant virus. Research indicates that alcohol consumption greater than 50 g/day (four or five drinks) is a risk factor for liver di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 101 publications
2
49
0
2
Order By: Relevance
“…More likely, and as articulated in previous work [35], the relations between memory functioning, HIV outcomes and alcohol use are reciprocal. Among HIVinfected individuals, problematic alcohol use is associated with worse HIV health outcomes [e.g., 2,5,7,8,[11][12][13][14][15][16][17][18][19] which ostensibly result in increased HIV symptom severity and lower overall quality of life. Adding to the clinical profile, HIV disease progression (i.e., heightened symptom burden) is commonly associated with neurocognitive impairment [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More likely, and as articulated in previous work [35], the relations between memory functioning, HIV outcomes and alcohol use are reciprocal. Among HIVinfected individuals, problematic alcohol use is associated with worse HIV health outcomes [e.g., 2,5,7,8,[11][12][13][14][15][16][17][18][19] which ostensibly result in increased HIV symptom severity and lower overall quality of life. Adding to the clinical profile, HIV disease progression (i.e., heightened symptom burden) is commonly associated with neurocognitive impairment [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both HIV and problematic alcohol use have significant implications for memory functioning, which is vital to successful adherence to complicated medication regimens and effectiveness of cognitive and behavioral interventions for HIV. Although previous research has shown that heavy alcohol use is associated with a host of negative HIV health outcomes, including poor medication adherence [2,7,8,[11][12][13][14][15][16], increased immune suppression [15,17,18], reduced effectiveness of therapeutic regimens [5], faster HIV disease progression [19], lower survival rates [20], and worse health-related quality of life [21], less is known about its impact on self-reported memory functioning and HIV symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…As enzimas hepáticas que atuam na biotransformação do álcool também estão envolvidas na catálise das moléculas de ARVs (por exemplo, álcool desidrogenase, aldeído desidrogenase, xantina oxidase, epóxido hidrolase e isoenzimas do citocromo P450) 7,157 . Portanto, os pacientes HIV+ que apresentam TUA e que estão sob terapia com ARVs são predispostos a interações farmacológicas que podem diminuir ou aumentar de forma inadequada os efeitos das moléculas de ARVs.…”
Section: Relações Farmacológicas Entre áLcool E Arvsunclassified
“…79 Although these findings are encouraging, it is widely reported that a history of injection drug use, alcohol use, and other substance use is associated with lower adherence to HAART 80,81 and that this group is therefore at increased risk for antiretroviral drug resistance. 82,83 There is preliminary evidence that individuals with resistance may be at increased risk for engaging in higher levels of risk behavior 15 and that the prevalence of ART resistance is high among some populations. 82 Resistance testing among those with treatment failure, therefore, may be important for groups such as drug users who may be at increased risk for transmitting drug-resistant HIV strains to sexual and needle-sharing partners and may actually benefit all individuals prior to HAART initiation.…”
Section: Needs For Building Evidence-based Approaches To Risk Reductimentioning
confidence: 99%